2018
DOI: 10.1093/geronb/gbx183
|View full text |Cite
|
Sign up to set email alerts
|

Memory Deficits Precede Increases in Depressive Symptoms in Later Adulthood

Abstract: In later adulthood, lower memory performance at a given age predicts subsequent 2-year increases in depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 39 publications
0
23
0
2
Order By: Relevance
“…Until now, the few longitudinal studies to examine reciprocal lead-lag relations between cognition and depressive symptoms have primarily focused on memory deficits (Aichele & Ghisletta, 2018; Jajodia & Borders, 2011; Perrino et al, 2008). Apart from the difference in cognitive measures used (i.e., fluid intelligence vs. memory), the current results are consistent with these earlier studies in showing that cognitive deficits temporally precede increases in depressive symptoms in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, the few longitudinal studies to examine reciprocal lead-lag relations between cognition and depressive symptoms have primarily focused on memory deficits (Aichele & Ghisletta, 2018; Jajodia & Borders, 2011; Perrino et al, 2008). Apart from the difference in cognitive measures used (i.e., fluid intelligence vs. memory), the current results are consistent with these earlier studies in showing that cognitive deficits temporally precede increases in depressive symptoms in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…We chose an alpha criterion of .01 for significance testing of changes in model fit and for parameter estimates. Although studies in the behavioral sciences typically select an alpha criterion of .05, it is not uncommon to find more conservative alpha criteria in population-based lifespan psychology studies, given their relatively large sample sizes (e.g., Aichele & Ghisletta, 2018; Jajodia & Borders, 2011). Selection of each model was guided by its Schwarz weight, that is, its weighted Bayesian information criterion, or w(BIC), rescaled as a relative probability of model preference, as explained by Wagenmakers and Farrell (2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 We adopted a step-by-step modelling strategy. [35][36][37] The fitted models included dynamic parameters: coupling and auto-proportional effects. BLCSM1 did not include crosslag paths between cognitive resources and physical activity and served as the baseline comparison model.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Survey of Health Ageing and Retirement in Europe (SHARE) study has demonstrated that lower memory performance at a given age predicted subsequent 2-year increase in depressive symptoms. For each 1-point decrement on a 10-point memory scale there was a 14.5% increased risk of depression two years later [34]. These bidirectional relations may be due to a shared common pathogenic pathway that includes insulin resistance, persistent hyperglycaemia, repeated episodes of hypoglycaemia, mitochondrial dysfunction, oxidative stress, advanced glycation end products, reduced cerebral amyloid clearance, diabetes-related complications and vascular disease [35,36].…”
Section: Diabetes-cognition-mood Interactionmentioning
confidence: 99%